Displacement and strain field assessment of PDMS using digital image correlation - Mendonça, Bebiana Alexandra Bragança (2014)
The main goal of this work is the characterization of the hyper-elastic mechanical behaviour of PDMS. The special specimens of PDMS (Sylgard® 184) were tested in a bi-axial tensile machine. The displacement and strain fields were measured using a commercial digital image correlation system (ARAMIS of GOM) during the tensile test. The experimental measurements are compared with numerical simulations, which use the most popular algorithms of constitutive models to characterize the hyper-elastic behaviour.